2019
DOI: 10.3390/nu11051000
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Regulates BDNF, trkB, PSA-NCAM, and Arc Expression in the Rat Cerebral Cortex after Bilateral Common Carotid Artery Occlusion and Reperfusion

Abstract: The polyphenol resveratrol (RVT) may drive protective mechanisms of cerebral homeostasis during the hypoperfusion/reperfusion triggered by the transient bilateral common carotid artery occlusion followed by reperfusion (BCCAO/R). This immunochemical study investigates if a single dose of RVT modulates the plasticity-related markers brain-derived neurotrophic factor (BDNF), the tyrosine kinase trkB receptor, Polysialylated-Neural Cell Adhesion Molecule (PSA-NCAM), and Activity-regulated cytoskeleton-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 99 publications
(138 reference statements)
1
18
0
Order By: Relevance
“…Assessment of the BDNF densitometric values by a two-way ANOVA ( Table 1 ) revealed an effect of BCP ( p < 0.0001). The slight reduction of BDNF relative levels in the BCCAO/R rats (0.7592 ± 0.01 in sham rats vs. 0.6936 ± 0.004 in BCCAO/R rats) is consistent with previously published data [ 20 ]. Such a decrease was highly statistically significant with an unpaired t -test analysis ( p < 0.0001), however, it did not reach the statistical significance with the pair-wise contrasts run after the ANOVA.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Assessment of the BDNF densitometric values by a two-way ANOVA ( Table 1 ) revealed an effect of BCP ( p < 0.0001). The slight reduction of BDNF relative levels in the BCCAO/R rats (0.7592 ± 0.01 in sham rats vs. 0.6936 ± 0.004 in BCCAO/R rats) is consistent with previously published data [ 20 ]. Such a decrease was highly statistically significant with an unpaired t -test analysis ( p < 0.0001), however, it did not reach the statistical significance with the pair-wise contrasts run after the ANOVA.…”
Section: Resultssupporting
confidence: 93%
“…So far, evidence in this area of research shows that the acute transient bilateral common carotid artery occlusion followed by reperfusion (BCCAO/R) is a model that can mimic in vivo the biological effects of acute cerebral oxidative stress and the early formation of a deleterious pro-inflammatory milieu [ 9 , 10 ]. Indeed, evidence shows that the BCCAO/R affects the brain tissue physiological homeostasis as early as 30 min [ 11 , 12 ] after surgery and appears to directly correlate to molecular marker adaptive changes in brain tissue and plasma [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, several studies have shown that treatment of mice with RSV does result in improvements in memory and cognitive function: Labban et al [ 127 ] saw improvements in a passive avoidance task in an AD mouse model with RSV (male SWR/J mice, 40 mg/kg/day RSV via IP, AlCl 3 induced NFT), Palomera-Avalos et al [ 128 ] showed improvements in novel object recognition (NORT) and open field tests (OFT) in a metabolically impaired model (22 month old C57BL/6J mice, high-fat diet (HFD) 60% calories from fat, 160 mg/kg/day RSV from chow), and Cao et al [ 129 ] (Male/female Sprague–Dawley rats, 100 mg/kg/day RSV from chow) similarly showed RSV-induced cognitive improvements in t -test exploration/success rates as well as improvements in Morris Water Maze (MWM) escape latency. RSV has also been reported to induce increases in early-LTP markers Arc and PSA-NCAM, BDNF [ 130 ], and late-LTP markers synaptophysin, PSD95, PSD93, and CREB in models of cerebral vascular disease [ 131 ], as well as regulate AMPAR expression and NDMA-mediated Ca 2+ influx [ 132 ]. These studies are promising in that they suggest that RSV can improve global cognition in disease states and that at least a portion of RSV’s improvements could come from improved synaptic protein expression, which is likely driven through SIRT1 activation of CREB [ 133 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Many studies report that RSV induces pro-synaptic plasticity effects, be it through changes in LTP-inducing proteins or morphological changes in synaptic structure [ 127 , 129 , 130 , 132 , 133 ]. While it is certainly true that increased synaptic expression of LTP-inducing proteins [ 47 ] and morphological changes [ 60 ] can be directly linked to improvements in cognition, it is important to demonstrate that these changes in expression will result in the increased translocation of key proteins to the synapse, and that this results in improvements in synaptic transmission rates.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%